The Relation between Arabic Linguistics and Islamic Legal Reasoning: Islamic Legal Theory Perspective - Anwar, Syamsul (Al-Jamiah: Journal of Islamic Studies, 2017)
In this article, the writer studies the relation between Arabic linguistics and the process of Islamic legal reasoning from an Islamic legal theory perspective. The question raised regards how Muslim jurists and legal theoreticians perceive the importance of Arabic linguistics as a part of the methodological tool in extracting Islamic legal norms from their sources, the connection of the two disciplines in theoretical level, and their mutual influences. The study shows that Muslim jurists and legal theoreticians agree unanimously that Arabic language mastering is an indispensable condition for a mujtahid to be valid. Further, Muslim jurists and legal theoreticians rely heavily in many cases on the grammatical rules set by the Arab grammarians and integrate these rules into the construction of their legal theory. Nevertheless, they do not merely transfer these rules as such into uá¹£Å«l al-fiqh but develop them to the extent to which the grammarians themselves do not attain.[Dalam artikel ini, penulis menelaah hubungan antara ilmu bahasa Arab dengan proses penetapan hukum Islam dari perspektif ilmu uá¹£Å«l al-fiqh. Pertanyaan yang dibahas berkisar pada bagaimana para fukaha dan teoretikus hukum memahami pentingnya bahasa Arab sebagai bagian dari metodologi dalam menetapkan norma-norma hukum Islam dari sumbernya, hubungan antara ilmu bahasa Arab dan ilmu uá¹£Å«l al-fiqh dalam tataran teoretis, serta pengaruh timbal balik antara dua disiplin ilmu tersebut. Studi ini menunjukkan bahwa para fukaha dan teoretikus hukum sepakat bahwa penguasaan bahasa Arab merupakan syarat mutlak bagi seorang mujtahid agar ijtihadnya sahih. Lebih jauh, dalam banyak kasus, para fukaha dan teoretikus hukum sangat bergantung pada aturan-aturan gramatika yang ditetapkan oleh para ahli tata bahasa Arab dan mengintegrasikan aturan-aturan ini ke dalam konstruksi teori hukum mereka. Namun demikian, mereka tidak hanya mengalihkan aturan-aturan ini ke dalam teori uá¹£Å«lal-fiqh tetapi mengembangkannya lebih jauh sesuai yang keperluan.]Â Â